Development of a montessori-based hijaiyah letter learning module in TPQ education West Papua - Siti Kamariyah; Hasbullah Hasbullah; Fardan Abdillah M; Agus Salim (Program Studi Pendidikan Agama Islam STAI Auliaurrasyidin Tembilahan, 2026)
This study developed the effectiveness of a Montessori-based Hijaiyah learning module at Al-Islami Quran Education Garden (TPQ), Fakfak District, West Papua, Indonesia. The study addressed the limitations of traditional rote-based instruction by introducing a child-centred approach emphasizing sensory learning and learner independence. A quasi-experimental design employing a one-group pretest–post-test model was conducted over six months through ten class meetings. The population comprised 244 TPQ students, and then 32 participants were selected using purposive sampling. The research involved three stages: module development, expert validation, and field testing. Data were collected through Hijaiyah literacy tests measuring letter recognition and pronunciation, a multimedia expert validation questionnaire consisting of 16 Likert-scale items, and semi-structured interviews with six students, two teachers, and one institutional leader. Quantitative data were analyzed using descriptive statistics, while qualitative data were examined through thematic analysis. The findings revealed a substantial improvement in students’ learning outcomes, with mean scores increasing from 61.8 on the pretest to 80.2 on the post-test. Expert validation yielded a 95.33% feasibility score, indicating excellent instructional quality and alignment with Montessori principles. Qualitative findings demonstrated enhanced student engagement, motivation, and learning independence. The study concludes that the Montessori-based module is an effective and feasible innovation for improving Hijaiyah literacy in TPQ settings.